Evaluación de los efectos del fracturamiento hidráulico sobre el comportamiento de producción en cuatro pozos del campo castilla norte mediante registros de producción, test de laboratorio y pruebas de productividad (2018)
In the present project an evaluation of the possible effects of the fractures is made, by the hydraulic stimulation or hydraulic fracturing in the production behavior of the deposit, taking into account the history of production and the petrophysical properties of the four proposed wells. To achieve the silver targets and the expected results, the PLT production records, well tests with the history and production conditions are taken, with which the production analysis is simulated, with the nodal analysis software. Additionally, a financial evaluation is carried out that allows the decision-making regarding the implementation of the operation. Since, the current production situation of Campo Castilla lies in the strange post-fracture condition, where there is a decrease in the water cut and an increase in oil production, taking into account that after the operation a significant increase is expected. in the production of the wells in the first three months of stabilization in obtaining surface fluids. The project is developed in an environment focused on the analysis of production and deposits, elaborating the collection of the previous and subsequent information of the candidate wells, including mechanical states, electrical and production records, laboratory tests, nodal analysis, and fracture designs. that throw the data necessary for the corresponding study of the effect of hydraulic fracturing.